2012
DOI: 10.1111/j.1365-2044.2012.07086.x
|View full text |Cite
|
Sign up to set email alerts
|

Translation of sonoelastography from Thiel cadaver to patients for peripheral nerve blocks*

Abstract: SummaryUltrasound guidance is now common in regional anaesthesia practice, but remains limited by poor visibility of the needle tip and poor quantification of local anaesthetic spread. Sonoelastography based on tissue compression is a technique depicting tissue strain. Hitherto used largely for tumour diagnosis, we used it in both Thiel embalmed cadavers and two patients receiving interscalene and femoral blocks to observe changes in tissue strain during local anaesthetic injection. The primary aim of our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…However, the financial efforts have to be weighed against the tissue characteristics resulting from the fixation agents. As shown in our study and by others (Thiel, ; Wolff et al, ; Benkhadra et al, ; Pattanshetti and Pattanshetti, ; Jaung et al, ; Hölzle et al, ; Munirama et al, ; Prasad et al, ; Eisma et al, ), Thiel‐fixed donors provide outstanding visual and haptic properties. Our modifications may likely aid saving costs in order to make the Thiel technique available to a broader user group (Benkhadra et al, ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the financial efforts have to be weighed against the tissue characteristics resulting from the fixation agents. As shown in our study and by others (Thiel, ; Wolff et al, ; Benkhadra et al, ; Pattanshetti and Pattanshetti, ; Jaung et al, ; Hölzle et al, ; Munirama et al, ; Prasad et al, ; Eisma et al, ), Thiel‐fixed donors provide outstanding visual and haptic properties. Our modifications may likely aid saving costs in order to make the Thiel technique available to a broader user group (Benkhadra et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…The wide range of joint motion allows orthopedic and trauma surgeons to perform interventions under realistic conditions, which is not the case after ethanol and formaldehyde fixation. Thiel fixation is also suitable for training laparoscopic techniques (Pattanshetti and Pattanshetti, ; Prasad et al, ) and ultrasound‐assisted interventions such as biopsies and nerve blocks (Munirama et al, ). Even muscle‐ or skin‐flaps can be accomplished by head and neck (Alberty et al, ), plastic (Wolff et al, ), oral surgeons and implantologists (Hölzle et al, ), since the Thiel fixatives prevent blood clot formation.…”
Section: Discussionmentioning
confidence: 99%
“…used sonoelastography to study the interstitial, intra-arterial, and intraneural spread of local anesthetics in Thiel cadavers and found that these can be used for objective assessment of the learning. [827] These cadavers can also be used for testing new technology and developing new techniques in UGRA. [5]…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been done on a supraomohyoid plexus block to avoid complications or collateral effects on other nerves (Feigl et al, 2006) and the spread of local anesthetic to block peripheral nerves (Munirama et al, 2012). For their part, Feigl et al (2013b), identified a simple orientation mark to carry out the vertical obturator nerve block.…”
Section: Authorsmentioning
confidence: 99%